Geochemistry at DSDP Holes 80-550 amd 80-548 - Anne Marie Karpoff; Maurice Bourbon; Bruno Ancel; Pierre C de Graciansky (PANGAEA, 1985)
At Sites 548 and 550 of DSDP Leg 80 several condensed sedimentary sections contain various types of polymetallic crusts. The relationships between mineralogic and geochemical data in the sections have been studied in the context of the biostratigraphic and sedimentologic results. The diagenetic evolution during periods of low accumulation rate varies according to depth and sedimentary environment. At Site 548 on the continental margin, the phosphatic and manganiferous crusts are similar to those related to upwelling influences before Late Cretaceous deposition. At Site 550 the upper Paleocene cherts, deposited directly on oceanic crust, are overlain by pelagic brown clays containing diagenetic manganiferous concretions characterized by very high Sr and Ba contents. The origin of these small nodules is probably related to the authigenesis of fecal pellets. The upper Eocene indurated section is made up of authigenic zeolites, clays, and Fe-Mn phases and is similar to the volcanic-sedimentary deposits described in deep basins and seamounts of the Pacific. These crusts and a polynucleated nodule within the overlying sediments have geochemical characteristics (high Ni, Co, and Cu contents) similar to those formed in the deep ocean under volcanic influences during periods of low sedimentation rates or sedimentary hiatuses. Volcaniclastic material is ubiquitous and peculiarly abundant in Eocene sections and can be related to the volcanic formation of Iceland in the North Atlantic.
Supplement to: Karpoff, AM et al. (1985): Diagenetic polymetallic crusts at Sites 550 and 548 of Leg 80, northeastern Atlantic Ocean. In: De Graciansky, PC; Poag, CW; et al. (eds.), Initial Reports of the Deep Sea Drilling Project, Washington (U.S. Gov. Printing Office), 80, 823-844, https://doi.org/10.2973/dsdp.proc.80.133.1985